PENGARUH PENGENDALIAN KONFLIK DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA KANTOR PREBEKEL DESA SOBANGAN-MENGWI-BADUNG - I Gusti Bagus Alit Prayoga; Ni Nyoman Suryani; Sapta Rini Widyawati (VALUES, 2021)
Employee performance is the way employees work in a company during a certain period. Companies that have employees who are performing well are likely to have good performance. This study aims to analyze the influence of conflict control and organizational culture on employee performance at the Prebekel Office, Sobangan-Mengwi Village, Bandung. Data collection was carried out by distributing questionnaires and carried out on 51 employees. Data analysis in this study used the SPSS version 16.0 application. The sample was determined by the census method and the data testing techniques used included validity testing with a correlation coefficient (r)> 0.30, reliability testing with Cronbach's Alpha. Classic assumption test and multiple linear regression analysis, to test and prove the research hypothesis. The results of this study indicate that the conflict control variables and organizational culture have a positive and significant effect on employee performance at the Prebekel Office, Sobangan-Mengwi-Badung Village.